Managing Your Wine Fermentation to Reduce the Risk of Biogenic Amine Formation - Smit, Anita Y.; Engelbrecht, Lynn; Du Toit, Maret (Frontiers in Microbiology, 2012)
Biogenic amines are nitrogenous organic compounds produced in wine from amino acid precursors mainly by microbial decarboxylation. The concentration of biogenic amines that can potentially be produced is dependent on the amount of amino acid precursors in the medium, the presence of decarboxylase positive microorganisms and conditions that enable microbial or biochemical activity such as the addition of nutrients to support the alcoholic and malolactic fermentation (MLF) inoculated starter cultures. MLF can be conducted using co-inoculation or inoculated after the completion of alcoholic fermentation (AF) that may also affect the level of biogenic amine in the wine. This study focussed on the impact the addition of complex commercial yeast and bacterial nutrients and the use of different MLF inoculation scenarios could have on the production of biogenic amine in the wine. Results obtained with wine showed that in this study the amine that was influenced by nutrient addition was histamine. In the synthetic winemaking using 12 different treatments no clear tendencies were observed. It was shown that in certain conditions co-inoculation could reduce the amount of biogenic amines produced.